2017
DOI: 10.5005/jp-journals-10015-1452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 15% Carbamide Peroxide on the Surface Roughness and Adhesion of Streptococcus mutans to Microhybrid Composite Resin and Giomer

Abstract: Introduction: Adhesion of bacteria, especially Streptococcus mutans (S. mutans) , to the surface of tooth restorations is a factor in the etiology of secondary caries. Given the ever-increasing popularity of bleaching procedures, the aim of the present study was to evaluate adhesion of S. mutans and surface roughness (SR) of microhybrid composite resin and giomer subsequent to the application of 15% carbamide peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Although several factors with different intensities are efficacious in the discoloration of aesthetic restorative materials, lower pH, food color and bleaching are among the most essential factors involved in this process [5]. In the past, teeth with ugly appearance underwent more invasive therapies, such as prosthetic treatments, but nowadays, easier, cheaper and more efficient methods such as bleaching, which are widely accepted, have been proposed and have made bleaching a popular dental treatment technique in recent decades [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although several factors with different intensities are efficacious in the discoloration of aesthetic restorative materials, lower pH, food color and bleaching are among the most essential factors involved in this process [5]. In the past, teeth with ugly appearance underwent more invasive therapies, such as prosthetic treatments, but nowadays, easier, cheaper and more efficient methods such as bleaching, which are widely accepted, have been proposed and have made bleaching a popular dental treatment technique in recent decades [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of polymerization and crosslinking of the composite resin are important factors determining the effects of the solutions on it [26]. The degree of polymerization depends on factors such as the type and intensity of the polymerization device, the color, the translucency, the opacity and the thickness of the composite resin [27][28][29]. In Bis-GMA-based composite resins, the degree of polymerization varies between 45% and 85% and it has been reported that the composite resins with Bis-GMA and UDMA base (similar to the composite resins used in this study) have a 20% lower degree of polymerization than the other monomers [30]; the low polymerization degree causes the materials to be more susceptible to degradation, resulting in reduced color stability and the release of products like methacrylic acid and formaldehyde can aggravate color change [26,30].…”
Section: Discussionmentioning
confidence: 99%